Pedagogia da terra na UFSCar: uma análise acerca da proposta metodológica e das práticas educativas da turma Helenira Resende - Silva, Paula da (2013)
Our goal in this paper is to report and try to analyze the methodological approach and the pedagogical practices of the first Field Education Course conducted by INCRA and PRONERA in partnership with the Universidade Federal de São Carlos and Social Movements of the field, between the years 2008 and in 2011. For this we used a literature review, participatory research and data analysis. We started the work with a brief contextualization of social and economic conditions that trigger land struggles, then we characterize the four social movements struggling for land that participated in the planning, development and evaluation of the course. Given the role of the Movimento dos Trabalhadores Rurais Sem Terra MST, in the fight for land and rural education and have a better defined educational proposal, we list as a parameter to the proposals and actions of course. Then, in the second chapter, devote ourselves to education in the MST, your concept of school and the Pedagogy of Movement, and approach the issue of rural education and the contribution of PRONERA in its consolidation. Finally, in the third chapter we highlight our object, featuring the gang Helenira Resende, pioneered the Pedagogy Course Earth in the State of São Paulo, and reporting pedagogical and methodological approach of the course, in addition to practices performed during the four years, thus, we describe the evaluation process, the organization of the steps, the stage, the pedagogical practices in communities, the community, the times and educational spaces, in addition to mechanisms for monitoring the course. Thus, we seek to contribute to this account future research and the construction of memory of Pedagogy in the Field, in São Paulo and Brazil.